EFFICIENCY OF DYNAMIC ELECTRONEUROSTIMULATION IN KNEE OSTEOARTHRITIS: RESULTS OF A MULTICENTER RANDOMIZED STUDY - O. M. Lesnyak; E. Yu. Kadochnikova; L. I. Alekseeva; I. G. Dydykina; O. B. Ershova; E. M. Zaitseva; T. A. Korotkova; T. A. Popova; M. L. Sukhareva; E. A. Taskina; V. N. Khodyrev; E. P. Sharapova; et al. (Научно-практическая ревматология, 2015)
Dynamic electroneurostimulation (DENS) is a type of percutaneous electroneurostimulation with a differentiation approach to choosing exposure areas and to optimizing electrocutaneous therapeutic action on the reflexogenic areas and acupuncture points for analgesia and for the treatment of functional disorders.Objective: to study the clinical efficiency and safety of therapy using a DiaDENS-PC apparatus in the treatment of knee osteoarthritis (OA).Subjects and methods. A multicenter randomized double-blind placebo-controlled study was conducted in 132 knee OA patients with pain value above 40 mm on visual analogue scale (VAS) and Lequesne’s index of 4–12. In a study group (n = 66), DENS was carried outwith a DiaDENS-PC apparatus using a trailing electrode applicator to the knee target in a Therapy stimulation mode at a frequency 77 Hz, a power of 15 units. In the placebo group, the similar procedure was performed with a switched-on placebo apparatus that did not differ in appearance from the working apparatus; but produced no electrical pulses. The treatment cycle consisted of 10 sessions lasting 30 min. Changes in Lequesne’s algofunctional index were primary end point. The results of the Get-Up to Go test (in seconds) and changes pain on VAS and WOMAC were used as secondary end points.Results and discussion. Both groups showed a statistically significant reduction of painand improvement of Get-Up and to Go test results by the end of the treatment course (p < 0.0001). Therewas a statistically significant difference in pain in the compared groups after a treatment session during the first (p = 0.037) and second (p = 0.010) visits. The analgesic effect of therapy was observed to persist in the DENS group 2 weeks (p = 0.006) and 1 month (p = 0.070) after treatment termination. After 10 sessions, there was a statistically significant difference between the groups in the Get-Up and Go test (p = 0.033) and Lequesne’s index (p = 0.022). Both groups exhibited a significant decrease in the total WOMAC scores. In the DENS group, positive changes in all subscales were statistically significant starting from the second visit whereas in the control group, the total WOMAC scores improvedonly at the expense of the pain subscale.